2021
DOI: 10.1155/2021/6308255
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect of Melatonin in Preterm Newborns

Abstract: Introduction. Preterm infants are at risk of free radical-mediated diseases from oxidative stress (OS) injury. Increased free radical generation has been demonstrated in preterm infants during the first seven days of life. Melatonin (MEL) is a powerful antioxidant and scavenger of free radicals. In preterm neonates, melatonin deficiency has been reported. Exogenous melatonin administration appears a promising strategy in the treatment of neonatal morbidities in which OS has a leading role. Objective. The aim w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
1
20
0
1
Order By: Relevance
“…However, the design of this study used the radioimmunoassay method and not randomized premature infants based on birth weight. Deficiency of the powerful antioxidant melatonin was the basis for studying the effect of increasing in blood levels in premature infants by oral supplementation [17]. The study included 36 premature weighing more than 1700 g. However, outcomes have not been studied.…”
Section: Methodsmentioning
confidence: 99%
“…However, the design of this study used the radioimmunoassay method and not randomized premature infants based on birth weight. Deficiency of the powerful antioxidant melatonin was the basis for studying the effect of increasing in blood levels in premature infants by oral supplementation [17]. The study included 36 premature weighing more than 1700 g. However, outcomes have not been studied.…”
Section: Methodsmentioning
confidence: 99%
“…Complementary adjunctive and immunomodulatory therapies are required to reverse immune system dysfunction and cytokine dysregulation. Melatonin is also known to have anti-inflammatory [ 15 ], antioxidant [ 16 ], immunomodulatory [ 17 ] and antiviral [ 18 ] infectious activities. It may be useful to use melatonin together with REGN-COV2 in elderly and other high-risk patients as an adjuvant to vaccines against the Omicron variant of SARS-CoV-2infection.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the low effectiveness of hypothermia is a driving force for the urgent development of adjunct pharmaceutical agents 1 . Melatonin, a hormone well known for its involvement in the circadian rhythm, was tested in preclinical trials for perinatal NE and demonstrated neuroprotective effects by pleiotropic and immunomodulatory mechanisms 2–4 . Moreover, our group was the first to define the pharmacokinetic profile of 0.5 mg/kg melatonin given orally over 4 h. This dosage was given to five neonates with NE undergoing therapeutic hypothermia.…”
Section: Introductionmentioning
confidence: 99%
“…1 Melatonin, a hormone well known for its involvement in the circadian rhythm, was tested in preclinical trials for perinatal NE and demonstrated neuroprotective effects by pleiotropic and immunomodulatory mechanisms. [2][3][4] Moreover, our group was the first to define the pharmacokinetic profile of 0.5 mg/kg melatonin given orally over 4 h. This dosage was given to five neonates with NE undergoing therapeutic hypothermia. The highest plasma concentration occurred between 3 and 12 h after the completion of the infusion, which was a longer half-life to compare animals and human adults.…”
Section: Introductionmentioning
confidence: 99%